2016
DOI: 10.1371/journal.pone.0168072
|View full text |Cite
|
Sign up to set email alerts
|

All Trans Retinoic Acid, Transforming Growth Factor β and Prostaglandin E2 in Mouse Plasma Synergize with Basophil-Secreted Interleukin-4 to M2 Polarize Murine Macrophages

Abstract: In previous studies we found that macrophages (MФs) from SH2-containing inositol-5′-phosphatase (SHIP) deficient mice are M2 polarized while their wild type (WT) counterparts are M1 polarized and that this difference in MФ phenotype can be recapitulated during in vitro derivation from bone marrow if mouse plasma (MP), but not fetal calf serum, is added to standard M-CSF-containing cultures. In the current study we investigated the mechanism by which MP skews SHIP-/- but not +/+ MФs to an M2 phenotype. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Our study demonstrated for the first time that IL-4 is not only an activator of the STAT6 signaling pathway but also a downstream effector in the TME that acts as a positive feedback factor. IL-4 promotes polarization into the M2-Mϕ phenotype and promotes tumor progression (47). We observed that tumor cells secrete lower levels of IL-4 after being cocultured with STAT6 −/− CD11b + cells, indicating that the pathway regulating IL-4 secretion pathway is inhibited by STAT6 deficiency in CD11b + cells but not tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated for the first time that IL-4 is not only an activator of the STAT6 signaling pathway but also a downstream effector in the TME that acts as a positive feedback factor. IL-4 promotes polarization into the M2-Mϕ phenotype and promotes tumor progression (47). We observed that tumor cells secrete lower levels of IL-4 after being cocultured with STAT6 −/− CD11b + cells, indicating that the pathway regulating IL-4 secretion pathway is inhibited by STAT6 deficiency in CD11b + cells but not tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…atRA also inhibits the LPS-induced production of the proinflammatory cytokines TNF- α and IL-12 and potentiates IL-10 production in the THP-1 monocyte/macrophage cell line and human cord blood mononuclear cells (CBMCs) [ 63 ]. Plasma factors, such as transforming growth factor- (TGF-) β and PGE2, in combination with RA, act synergistically with IL-4 synthesized by basophils to increase the sensitivity of macrophages to IL-4, which contributes to M2 macrophage polarization and the regulation of the inflammatory process in mice [ 64 ].…”
Section: Effects Of Ra On Immune Cellsmentioning
confidence: 99%
“…SHIP also blocks IL‐3 induced M2‐like Mϕ skewing, which can now been attributed to enhanced IL‐4 production by IL‐3‐treated SHIP −/− basophils . Hyperresponsive SHIP −/− basophils are the source of IL‐4 driving M(IL‐4) activation in vivo in the SHIP −/− mouse …”
Section: Macrophagesmentioning
confidence: 96%